Intervensi Kemanusiaan ke Libya: Refleksi Politik - Jerry Indrawan (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2018)
Judging from humanitarian reasons, indeed at that time there have been quite a number of casualties, therefore intervention in Libya can be justified to prevent victims from increasing. So morally, intervention in Libya was done to save Libyan civilians from Moammar Gaddafi's cruelty. However, the problem is not that simple. Resolutions issued regarding the legality of humanitarian intervention to Libya by the UN Security Council, namely numbers 1970 and 1973, not only refer to articles 41 and article 42, but must also consider article 39 of the United Nations Charter. Based on article 39 it is emphasized that the word peace must refer to international peace. Because, there will be a contradiction if the UN Security Council interferes with a civil dispute that is not classified as an international peace threat. In addition, of course political and economic motives, clearly such actions are a violation of international law.